2021
DOI: 10.1093/jnci/djab036
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Cancer Risk in Women With Germline BRCA1 or BRCA2 Mutations: Multicenter Cohort Study

Abstract: Background Endometrial cancer (EC) risk in BReast CAncer gene 1/2 (BRCA1/2) mutation carriers is uncertain, therefore we assessed this in a large Dutch nationwide cohort study. Methods 5,980 BRCA1/2 (3,788 BRCA1, 2,151 gBRCA2, 41 both BRCA1/BRCA2) and 8,451 non-BRCA1/2 mutation carriers were selected from the HEBON-cohort. Follow-up started at date of nationwide PALGA coverage (January 1, 1989) or at the age of 25 years (whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 35 publications
2
55
2
1
Order By: Relevance
“…Recently, in a prospective cohort study of BRCA carriers who received only RRSO, not hysterectomy, endometrial cancer developed in eight patients in a median follow-up of 5.1 years, with no apparent increased risk after RRSO, on the other hand, BRCA1 carriers had an increased risk of endometrial serous adenocarcinoma [ 92 ]. Furthermore, a large Dutch nationwide cohort study revealed that BRCA1/2 carriers have a 2- to 3-fold increased risk for endometrial cancer, with the highest risk observed for the rare subgroups of serous-like and p53-abnormal endometrial cancer in BRCA1 carriers [ 93 ].…”
Section: Differences Of Other Brca -Related Cancers Risks By Brca1/2 Mutationmentioning
confidence: 99%
“…Recently, in a prospective cohort study of BRCA carriers who received only RRSO, not hysterectomy, endometrial cancer developed in eight patients in a median follow-up of 5.1 years, with no apparent increased risk after RRSO, on the other hand, BRCA1 carriers had an increased risk of endometrial serous adenocarcinoma [ 92 ]. Furthermore, a large Dutch nationwide cohort study revealed that BRCA1/2 carriers have a 2- to 3-fold increased risk for endometrial cancer, with the highest risk observed for the rare subgroups of serous-like and p53-abnormal endometrial cancer in BRCA1 carriers [ 93 ].…”
Section: Differences Of Other Brca -Related Cancers Risks By Brca1/2 Mutationmentioning
confidence: 99%
“…Moreover, previous reports have suggested that BRCA1 pathogenic variants elevate the risk of the aggressive serous EC subtype in particular (Ring et al, 2016; Saule et al, 2018; Shu et al, 2016), a subtype with even later age at onset than other more common EC subtypes (Setiawan et al, 2013). Interestingly, a recent publication estimating standardized incidence ratios for EC in the Dutch population identified an increased risk of serous EC associated with BRCA1 and BRCA2 pathogenic variants, with significantly increased risk also detectable for endometrioid subtype for BRCA1 but not BRCA2 pathogenic variant carriers (de Jonge et al, 2021). Unfortunately, due to a lack of relevant information, we could not investigate if pathogenic variants occurred more often in women with serous EC subtype in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, cumulative risks of EC at 75 years of age remain low. 61 Riskreducing hysterectomy may be an option during RRSO, but the potential for increased complications and uterine lesions must be considered.…”
Section: Hereditary Breast and Ovarian Cancermentioning
confidence: 99%